Efficacy and safety of recently approved drugs for sickle cell disease: A review of clinical trials (2020)
Sickle cell disease is prevalent in several parts of the world. Most of the hospitalizations in these patients are related to pain crisis episodes. Moreover, the levels of hemoglobin are lower in sickle cell disease patients as compared to the general population. Complications related to sickle cell disease are managed with blood transfusions, hydroxyurea, and opioids. Despite these therapies, patients with sickle cell disease experience multiple pain crisis episodes leading to hospitalizations and end-organ damage. FDA has approved three new drugs, L-glutamine, voxelotor, and crizanlizumab, for the prophylaxis and treatment of complications related to sickle cell disease. This review aims to assess the efficacy and safety of recently approved drugs for the treatment of sickle cell disease. A comprehensive search was made on PubMed and clinicaltrials.gov to look for clinical trials reporting the efficacy and safety of recently approved drugs for sickle cell disease. Based on the results of clinical trials, L-glutamine, voxelotor and crizanlizumab were well tolerated by sickle cell disease patients. L-glutamine and crizanlizumab reduced the number of sickle cell crisis episodes, while voxelotor improved the level of hemoglobin in sickle cell disease patients. These drugs were effective alone and in combination with hydroxyurea.